Can insulin signaling pathways be targeted to transport Aβ out of the brain? - Vandal, Milene; Bourassa, Philippe; Calon, Frédéric (Frontiers in Aging Neuroscience, 2015)
Although the causal role of Amyloid-β (Aβ) in Alzheimer’s disease (AD) is unclear, it is still reasonable to expect that lowering concentrations of Aβ in the brain may decrease the risk of developing the neurocognitive symptoms of the disease. Brain capillary endothelial cells forming the blood-brain barrier (BBB) express transporters regulating the efflux of Aβ out of the cerebral tissue. Age-related BBB dysfunctions, that have been identified in AD patients, might impair Aβ clearance from the brain. Thus, targeting BBB outward transport systems has been suggested as a way to stimulate the clearance of Aβ from the brain. Recent data indicate that the increase in soluble brain Aβ and behavioral impairments in 3xTg-AD mice generated by months of intake of a high-fat diet can be acutely reversed by the administration of a single dose of insulin. A concomitant increase in plasma Aβ suggests that clearance from the brain through the BBB is a likely mechanism for this rapid effect of insulin. Here, we review how BBB insulin signaling pathways could be stimulated to decrease brain Aβ concentrations and improve cognitive performance, at least on the short term.